The role of histamine on cognition - Alvarez Toro, Edgardo Orozimbo (2009)
Histamine was intensively studied at the beginning of the 20th century because of its important role in allergic and inflammation processes. In those days it was very difficult that researchers could envisage another impacting function for the imidazolamine in the living systems. Once the imidazolamine was found located in neuron compartment in the brain, increasing evidence supported many regulatory functions including its possible role in memory and learning. The specific participation of histamine in cognitive functions followed a slow and unclear pathway because the many different experimental learning models, pharmacologic approaches, systemic and localized applications of the histamine active compounds into the brain used by researchers showed facilitating or inhibitory effects on learning, generating an active issue that has extended up to present time. In this review, all these aspects are analyzed and discussed considering the many intracellular different mechanisms discovered for histamine, the specific histamine receptors and the compartmentalizing proprieties of the brain that might explain the apparent inconsistent effects of the imidazolamine in learning. In addition, a hypothetical physiologic role for histamine in memory is proposed under the standard theories of learning in experimental animals and humans.